Land Use Transitions in the Cerrado : Impacts on Ecosystems and Future Paths from the Perspective of the Water, Energy, and Food Nexus - Rodrigues, Ariane de Almeida (2023)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Ecologia, Programa de Pós-graduação em Ecologia, 2025.